Analisis Perilaku Tidak Rasional Keputusan Pembelian pada E-Commerce Shopee - Ade Tyo Denniswara; Donni Junipriansa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The rapid development of e-commerce in Indonesia has transformed consumer behavior from rational decision-making towards more irrational and emotional tendencies. This study aims to analyze the extent to which irrational behavior, particularly Fear of Missing Out (FOMO) and Herding Behavior, affects purchasing decisions among Shopee consumers in 2025. The research method applied is a descriptive quantitative approach using a Likert scale-based questionnaire as the main instrument. This study is expected to provide insights into the significant role of emotional and social aspects in shaping consumptive and impulsive behavior, as well as contribute to a better understanding of digital consumer behavior.